(untitled) (Bangladesh Journal of Botany, 2015)
The comparison of fatty acid content in Camellia oleifera (L.) Kuntze oil and olive oil was done by GC. C. oleifera oil contained more C18:1n9c, C18:2n6c, C20:1 and C22:1n9 than olive oil. Olive oil did not contain C21:0 and C24:1 but more C8:0, C16:0, C16:1, C18:0, C18:3n6, C18:3n3, C20:2, C22:0, C23:0 and C24:0 than C. oleifera oil, C. oleifera oil did not contain C20:2. C. oleifera oil and olive oil are beneficial for human health for their unsaturated fatty acids content and C. oleifera oil is healthy than olive oil. DOI: http://dx.doi.org/10.3329/bjb.v44i1.22741 Bangladesh J. Bot. 44(1): 155-157, 2015 (March)